Effect of Giving Crab Shells as a Source of chitin on the Yellow Cyst Nematode (Globodera rostochiensis W) Population on Potato (Solanum tuberosum L.) - Umarul Anshori Bin Asyar (Contributions of Central Research Institute for Agriculture, 2021)
This study aims to determine the effect of several concentrations of chitin on the NSK population and to determine the microbes (fungi) that act as chitinolytic microbes. The hypotheses put forward are (1) the higher the concentration of chitin, the lower the NSK population, (2) there are microbes (fungi) that act as chitinolytic microbes. to the soil at high concentrations. The best treatment capable of suppressing the yellow cyst nematode population and increasing the fresh weight of tubers was 0.5% chitin concentration. The results of isolation of soil microbes (fungi) before planting found 5 fungi that are chitinolic and capable of degrading chitin in cysts, namely Trichoderma sp., Paecilomyces sp., Aspergillus sp., Verticillium sp. and Penicillium sp., while the observation of 100 hst showed an increase in the fungus Trichoderma sp. from one species to four species. Potato (Solanum tuberosum L.) is an important horticultural commodity in Indonesia which is currently an alternative food ingredient, as a source of protein-rich carbohydrates to support food diversification programs (Rukmana, 1997). One of the important pests that are troubling farmers potatoes, especially in Malang district, East Java, is the Yellow Cyst Nematode (NSK). According to a report from the Ministry of Agriculture, in Indonesia in 2003 the area of infected plants was estimated at 25% of the total area of 800 hectares of potato plants. Control has been carried out well biologically and chemically. Alternatives for biological control include using materials that are unfavorable for the nematode environment, namely through the use of chitin.